Influence of Teachers Characteristics on their Attitudes towards the integration of ICT IN instruction Lower Primary Grades Curricula in the Middle Badia in Jordan - Aburayash, Hussen (Dirasat: Educational Sciences, 2022)
Objectives: The study aimed to find out the effect of teachers characteristics on their attitudes to wards the integration of information and communication technology (ICT) among teachers of the lower basic stage in the middle Badia in Jordan in teaching and learning. Methods: The study sample consisted of (210)male and female primary school teachers in the middle Badia schools in Jordan, they were chosen by the intentional method, and the data were collected through a questionair prepared by the researther , and the data were analyzed using both descriptive and inferential statistics. Results: The study proved that the characteristics of teachers (experience in teaching, computer competencies , and training on (ICT) are strong predictors of a teachers attitude towards (ICT). These characteristics have had an average impact on the integration of ICT in the teaching of the lower basic level courses in the middle Badia schools in Jordan, which supports the importance of this study and the training teachers need in order to acquire ICT skills and employ them in education. Conclusions: These results may help policy-makers and teacher to include (ICT) in pre-service and in-service teacher training.